Peran Guru Pendidikan Pancasila Dan Kebanggaan Dalam Penentuan Karakter Siswa Di Sekolah Dasar - Pratomo, Ikhsan Fauzi Cahyo; Rifqia, Muhammad Wafa; Sunaryati, Titin (Jurnal Ilmiah Wahana Pendidikan, 2023)
Civic education and Pancasila are crucial for developing kids' character in elementary school. Citizenship education and Pancasila Teachers serve as the main educators in the learning process, working to help students acquire attitudes, information, and abilities that are consistent with Pancasila principles and good citizenship. The goal of this study is to establish the significance of citizenship and Pancasila teachers in helping young children develop positive character traits. Data were gathered using a qualitative case study technique through observations of classes, interviews, and document analysis of Pancasila and citizenship education curriculum and learning materials. The findings indicated that teachers of Pancasila and Citizenship Education play a significant part in forming the character of primary school children